Response mechanism of water status and photosynthetic characteristics of Cotoneaster multiflorus under drought stress and rehydrated conditions - Huang, Qiu-liang; Zhang, Miao-miao; Li, Chang-shun; Li, Bo-yang; Zhuo, Sheng-lan; Yang, Yu-shan; Chen, Yu-da; Zhong, An-na; Liu, Hao-yang; Lai, Wen-feng; Huang, Zhen-bei; Cao, Ming-hui; et al. (Frontiers in Plant Science, 2025)
IntroductionPlant physiology response and adaptation to drought stress has become a hotspot in plant ecology and evolution. Cotoneaster multiflorus possesses high ecological, ornamental and economic benefits. It has large root system and tolerance to cold, drought and poor soil. Therefore, C. multiflorus is considered as one of the most important tree species for ecological restoration in arid and semi-arid areas. However, little is known about the physiological mechanisms, molecular mechanisms and drought strategies of how C. multiflorus responds to drought stress. Therefore, exploring the physiological response mechanisms, molecular mechanisms and adaptive strategies of C. multiflorus in response to drought is important for its growth in arid and semi-arid regions.MethodsWe investigated the response and coupling mechanisms of water status, photosynthetic properties and chloroplast fluorescence parameters in C. multiflorus in response to drought and rehydrated after drought, especially the importance of nocturnal sap flow and nocturnal water refilling to maintain its own water balance in response to drought stress. In addition, we studied the stress response of C. multiflorus transcriptome factors, and we also discussed drought adaptation strategies of C. multiflorus.ResultsC. multiflorus adapted to drought stress by a series of structural and physiological mechanisms, such as promoting closing stomata, increasing nocturnal sap flow. When rehydrated after undergoing severe drought stress, its physiological activities such as photosynthesis, water status, chlorophyll fluorescence parameters and other physiological activities have rapidly resumed. This showed C. multiflorus had strong tolerance to drought. In addition, water status, photosynthetic characteristics, and chloroplast fluorescence parameters of C. multiflorus were highly coupled. Nocturnal sap flow and nocturnal water refilling were very important for C. multiflorus to maintain its own water balance in response to drought stress. Finally, C. multiflorus will strengthen the drought defense mechanism by gene regulation of various metabolisms, such as promoting stomatal closure, reducing transpiration water loss, and vigorously regulating water balance. C. multiflorus responded to drought stress by avoiding or reducing water deficit in plant organs and tissues. Therefore, the shrub C. multiflorus is a drought-tolerant plant.DiscussionWe explored the response mechanisms of water status, photosynthetic characteristics, and chloroplast fluorescence parameters of C. multiflorus in drought and rehydrated after drought stress, especially the response mechanisms of nocturnal sap flow and nocturnal water refilling in response to drought stress, and identified the physiological coupling mechanisms, molecular mechanisms and drought types of C. multiflorus in response to drought.